Development of a support programme for nurses who care for patients with chronic illness in three Limpopo Province health institutions - Rikhotso, Tsakani Glory (My University, 2023)
Nurses working in mental health institutions experience enormous challenges sometimes without formal support structures and programmes to ease their caring duties. This study sought to develop a support programme for nurses caring for patients with chronic mental illness in three mental health institutions in Limpopo Province. A qualitative descriptive phenomenological design was used. A total of thirty participants (male = 7; females = 23) between 27 and 64 years were selected using a purposive homogeneous sampling method. Data were collected using in-depth semi-structured interviews. Hycner‘s adapted phenomenological explication method was used to analyse the data. Six primary themes and twenty-four sub-themes emerged during data explication. The six major themes include: the nature of chronic mental illness, professional nurses’ phenomenological experiences, challenges experienced by professional nurses (PNs), coping mechanisms used by PNs, support structures and programmes for PNs, and suggested support programmes for PNs. The first theme comprises common diagnoses as a sub-theme. Receiving and giving reports, personal hygiene, morning devotions, health education, giving patients medication, physical assessment, and administrative tasks emerged as sub-themes of the second theme. The third theme includes these sub-themes: shortage of staff, lack of social support, safety and security problems, lack of incentives, shortage of resources, and shortage of treatment. Prayer, belief in God, teamwork, self-counselling, and absenteeism are coping mechanisms used by nurses in the fourth theme. The fifth theme focuses on support structures and programmes. According to these PNs, there are no formal support structures or programmes available for nurses, except union forums, monthly meetings, and nurses’ day. Family support, support by colleagues and supervisors, psychological support, and general social support are sub-themes that emerged in the sixth theme. The study findings suggest that nurses would like a formal structured support programme to empower them with skills to manage their caring duties. From the findings of the study, a support programme was developed. The support programme emphasises the importance of social support systems, financial support, general support, and psychological support from relevant stakeholders. It is recommended thata developed support programme should be evaluated and implemented in mental health institutions. The findings have implications for nursing and psychology to work together to provide optimal and holistic support for nurses working in mental health institutions.
Thesis (Ph.D. (Psychology)) -- University of Limpopo, 2023
Keywords: Professional nurses; Patients; Chronic mental illness; Mental health institutions; Caring; Mental illness; Nursing ethics; Chronic diseases -- Psychological aspects; Health care teams -- Training of